Fixed bed reactors of non-spherical pellets: Importance of heterogeneities and inadequacy of azimuthal averaging. (February 2019) - Moghaddam, E.M.; Foumeny, E.A.; Stankiewicz, A.I.; Padding, J.T.
Graphical abstract: Highlights: RBD-CFD approach is validated for modeling hydrodynamics in fixed bed reactors. Local flow field and pressure drop in packings of spheres and cylinders. Inadequacy of azimuthal-averaging of 3D velocity fields in narrow beds. The method aids in advancing design of fixed bed reactors with non-spherical pellets. Abstract: Despite the substantial simplicities inherent in pseudo-continuum models of fixed bed reactors, there is a continued interest in the use of such models for predicting fluid flow and transport scalars. In this paper, we aim to quantitatively address the inadequacy of 2D pseudo-continuum models for narrow-tube fixed beds. We show this by comparing with spatially resolved 3D results obtained by a robust and integrated numerical workflow, consisting of a sequential Rigid Body Dynamics and Computational Fluid Dynamics (RBD-CFD) approach. The RBD is founded on a physics-based hard-body packing algorithm, recently proposed by the authors (Moghaddam, E.M., Foumeny, E.A., Stankiewicz, A.I., Padding, J.T., 2018. A Rigid Body Dynamics Algorithm for Modelling Random Packing Structures of Non-Spherical and Non-Convex Pellets. Ind. Eng. Chem. Res. 57, 14988–15007), which offers a rigorous method to handle resting contacts between particles. The methodology is benchmarked for simulations of flow fields in all flow regimes, for 5 ≤ Rep  ≤ 3, 000, in random packings of spheres and cylinders with tube-to-pellet diameter ratios, N, between 2.29 and 6.1. The CFD results reveal a remarkable influence of local structure on the velocity distribution at the pellet scale, particularly in low-N packings, where the spatial heterogeneity of the structure is very strong along the bed axis. It is also demonstrated that azimuthal averaging of the 3D velocity field over the bed volume, which has been considered as an advancement over plug flow idealization in classical pseudo-continuum models, cannot reflect the role of vortex regions emerging in the wake of the pellets, and leads to underestimation of the local velocity values by more than 400% of the inlet velocity.